Guarantee of fundamental rights through state functions in the execution of the public budget: an integrative review of scientific production in the last ten years (Research, Society and Development, 2020)
The article proposes to show which paths have been taken, which practices have been used and which have been addressed by the researchers when speaking of "Public Budget and the Functions of the State in Guaranteeing Fundamental Rights", seeking to answer the following question: Does the current budget model allow for the exercise of Fundamental Rights? For this purpose, a qualitative research was carried out based on the bibliographic review of the subject through articles researched in the CAPES journal platform of the last 10 years. As results we found evidence that in many cases the "Fundamental Rights" and the "Functions of the State" are neglected in the budget execution due to several factors, such as: Discretionary, authoritative budget, lack of planning and control in administrative actions, need for qualification in cutting public spending in search of fiscal balance, outsourcing of functions of the state and weakening of participatory processes of budget preparation.